Why Manifestos, why now? - Kent, Michael; Ellis, K.; Robertson, R.; Garland-Thomson, R. (Routledge, 2018)
This collection identifies the key tensions and conflicts being debated within the field of critical disability studies and provides both an outline of the field in its current form and offers manifestos for its future direction.